Evaluation of bank lending practices and credit management in Kazakhstan - Iskakova, K.; Ondassynova, T.; Seidualiyev, D.; Temirov, A. (International School of Economics KAZGUU, Nur-Sultan, 2022)
Back in 1987, the banking system of Kazakhstan had two banks. Kazakhstan's banking system has been developing since independence and has achieved incredible results. Thus, Kazakhstan occupies a leading position in the field of financial technologies developed by banks that are part of the banking system. In this article we evaluate the banking system of Kazakhstan, namely the practice of bank lending and credit management. We tested hypotheses to evaluate the system of bank lending. To do this, we resorted to quantitative, qualitative and empirical methods. In this study, we found out the main reason for the differences in the lending system, the factors of the lending system that determine profitability and efficiency; which segment of lending brings the greatest profit; the relationship of banking indicators such as NPL with net profit, loan portfolio and return on assets, and finally, the relationship of the introduction of prudential standards by the National Bank for the entire banking system of Kazakhstan.
Keywords: bank lending, credit management, credit management in Kazakhstan